Errors in English Essay Writing from a Syntactic Perspective - Hikmah, Istianatul (NOTION: Journal of Linguistics, Literature, and Culture, 2019)
This study discuses errors in English essay writing from syntactic perspective. Syntactic theory was used to analyze data while the data of this study were English essay writing written by university students. The method of this study was qualitative study which was divided into three namely data collecting method, data analysis method, and presentation of data analysis. Data of this study were collected using simak method. It meant monitoring the language used which was in the form of written text. Then there are two techniques used to collect data namely documentation and noted technique. Descriptive analytic was used to analyze data using syntactic theory. Informal method was used to present the result of data analysis in the form of sentences. There were two results of this study. Firstly, it showed that there were nineteen words, thirteen phrases, and thirteen clauses were found as errors in university students’ English essay writing. Secondly, university students need to master English grammar to minimize syntactic errors in English essay writing.     Keywords: syntactic errors, syntactic perspective, word, phrase, clause